Theoretical and perceived balance of power inside Spanish public hospitals - Schneider José; Salvadores Paloma; Zubero Imanol (BMC, 2001)
Abstract Background The hierarchical pyramid inside Spanish public hospitals was radically changed by the Health Reform Law promulgated in 1986. According to it, the manpower of the hospitals was divided into three divisions (Medical, Nursing, General Services/Administration), which from then on occupied the same level, only subject to the general manager. Ten years after the implementation of the law, the present study was designed in order to investigate if the legal changes had indeed produced a real change in the balance of power inside the hospitals, as perceived by the different workers within them. Materials and Methods A questionnaire was administered to 1,027 workers from four different public hospitals (two university-based and two district hospitals). The participants belonged to all divisions, and to all three operative levels (staff, supervisory and managerial) within them. The questionnaire inquired about the perceived power inside each division and hierarchical level, as well as about that of the other divisions and hierarchical levels. Results Every division attributed the least power to itself. The Nursing and the Administrative division attributed the highest power to the physicians, and these attributed the highest power to the General Services/Administrative division. All hierarchical levels (including the formal top of the pyramid) attributed significantly more power to the other than to them. Conclusions More than ten years after the implementation of the new law, the majority of workers still perceive that the real power within the hospitals is held by the physicians (whereas these feel that it has shifted to the administrators). No division or hierarchical level believes it holds any significant degree of power, and this carries with it the danger of also not accepting any responsibility.